An exploratory study on the preparation of metallic rhenium (Re) and ReO3 via non-contact solution plasma electrolysis - Hong Fu; Lingling Shen; Zhongning Shi; Nan Zhou; Qiangqiang Cheng; Wanan Lai (PLoS ONE, 2025)
Metallic rhenium (Re) and its oxides (e.g., rhenium trioxide ReO 3 ) have been extensively utilized in fields including national defense, aerospace, and electronics, owing to their unique “Re effect” and favorable thermal expansion characteristics. However, conventional preparation methods confront substantial scientific and technical challenges, primarily arising from the intrinsic physicochemical properties of Re and the complexity of synthesis processes. This study focused on the synthesis of ultrafine Re/ReO 3 composite particles via plasma electrolysis in aqueous solutions, employing a Re-containing precursor as the anode feedstock and a tungsten (W) wire as the cathode. The effects of key process parameters, including discharge voltage, electrolyte composition, solution acidity, and electrolysis duration on the morphological features of the resultant particles were systematically investigated. Additionally, plasma emission spectra, discharge behavior (encompassing cathode/anode voltage variations), electrolyte volume, and temperature evolution were monitored to elucidate the reaction mechanisms and dynamic behaviors governing the synthesis of different ultrafine powders. The results demonstrated that ReO 3 - Re composite powders can be successfully prepared using this method. Notably, reducing the discharge voltage suppressed W sputtering from the cathode and promoted the formation of ReO 3 as the dominant phase. Furthermore, the addition of H 2 SO 4 mitigated particle aggregation by enhancing hydrogen-bonding coordination among particles and electrolyte components.